Stakeholder Collaboration in Conservation and Tourism Area Management in Petengoran, Lampung Province - Hesty, Rein Susinda (Jurnal Arsitektur, 2025)
Petengoran Mangrove Forest is an ecotourism area located between Sari Ringgung Beach and Dewi Mandapa Beach, precisely in Gebang Village, Padang Cermin Subdistrict, Pesawaran Regency. This area is a mangrove forest conservation site initiated in 2009. The conservation efforts were driven by the need to prevent malaria outbreaks that emerged in the same year. Consequently, the community voluntarily started rehabilitating the mangrove area for conservation purposes. The opening of this conserved mangrove area as a tourism destination needs to be analyzed to avoid negative impacts on various aspects of life. Therefore, the purpose of this study is to identify the characteristics of the Petengoran Mangrove Forest and develop strategies for collaborative stakeholder management that consider both conservation and tourism landscapes. The research methodology employed a mixed-method approach, combining qualitative and quantitative analyses. Qualitative data were obtained from key informants, while quantitative data were collected using the Mental Modeler application to provide weighted considerations for the forest area as a conservation and tourism landscape. The results indicate that in the stakeholder scenario, by considering the involvement of the government, private sector, and non-governmental organizations, the highest values were assigned to regulation with a score of 0.06, conservation with a score of 0.02, and tourism with a score of 0.01.